Factors affecting the proliferation of caregiver agencies in Iloilo City - Calva, Loribelle M.; Calzado, Archie G.; Evangelista, Mechon M.; Galila, Desiree Joy H.; Garay, Don Lane L.
This paper is mainly focused on finding out the factors that affect the proliferation of Caregiver Agencies in Iloilo City. There were two chief sources from which information and integral data were attained. these were gathered through questionnaires and interviews that were distributed to recipient caregiver agencies (St. Paul's College of Iloilo, IMAP, BELFA, Lifeline) and their enrolled students. The Technical Education and Development Authority or TESDA attests their credibility. To substantiate the gathering of information process, the questionnaires were given to the students taking the caregiver courses and the researchers chose to take one (1) class size, with 25-35 students who are approximately ;less than or equal to 26 years old, with a median which depicts that they had earned Bachelor's degree or are college graduates, and typically comprised of females, per agency. These students are either married or not and with or without kids. On the other hand, the interviews were conducted with the manager or his/her authorized representative who has ample knowledge of his/her represented agency. Results shows that the primary reason why individuals succumb taking the caregiving course is because of the need for a job which is situated outside the country specifically Canada, US, London, etcetera, that will generate a higher and promising income which is most likely above the wage/salary received if one is employed here in the Philippines. At the same time believing that this will give them an easy access to go abroad. Palpably, most Filipinos believe that life in foreign lands is better than life here especially when most are currently unemployed. The greater percentage share of the respondents hesitated to disclose their occupation. The same result was driven out when questioned about their certain income level. In another aspect, majority of the respondents wants to work in hospitals and prefer working abroad at a maximum of five years although their were some who chose to be in this occupation for 21 years in contractual basis wherein after the said time span, they plan to stay or live in the same place to have a better life or tone with their settled relatives there. However, there are issues, which concern them. These are environmental stability and issues of Filipino being abused and harassed abroad. Thus, respondents expect full support and guidance from the agency responsible for their employment. After careful study and analysis, the researchers arrived to the conclusion that the Filipino colonial mentality is the core factor that affects the proliferation of Caregiver agencies in Iloilo City taking the point of view of the students. This had been passed from generation to generation and like a social cancer, this is somehow incurable unless attended by proficient and able government officials with the help of the people themselves. With the economic condition of the country at the moment, it would not be a surprise that the increasing desire and need to work abroad becomes prevalent especially when catalyzed by the rising demand of caregivers abroad also. On the other arena, that of the agencies' perspective, they rationalize that the demand for caregivers abroad motivate them. In the same way, this is the reason why there is a sizable growth of agencies in Iloilo. Needless to say, the starting point of these establishments is profit. Every business institution is profit-oriented.